Self-Harm in Indonesian Adolescents and Undergraduates (2015–2025): A Bibliometric and Science-Mapping Study with Guidance and Counseling Implications - Navion, Febranti Putri; Widyarto, Wikan Galuh; Azmi, Khilman Rofi'; Zuhdi, Muhammad Sholihuddin; Cahyono, Febri Tri; Machfud, Muchammad Saiful; Arifuddin, Alfan (Buletin Konseling Inovatif, 2025)
The objective of this study is to map a decade (2015–2025) of Indonesian research on self-harm among secondary-school students and undergraduates while examining its implications for guidance and counseling practice in schools and universities. The methods applied were a bilingual, population-bounded bibliometric design in which data were retrieved from Google Scholar using Publish or Perish (PoP), screened through a PRISMA-guided protocol, and analyzed with performance indicators such as annual output, sources, top documents, and citation trends, complemented by science-mapping techniques including keyword harmonization and VOSviewer-based co-word networks. The results show that from 440 records initially retrieved, 119 studies met the eligibility criteria, with research output accelerating significantly after 2021, peaking in 2024, and showing comparable momentum in 2025. Publications were dispersed across fragmented venues, with citations concentrated in a few national journals, and thematic clusters focused on adolescents, social media, cyberbullying, depression, anxiety, and suicidal ideation, while intervention models, validated measurement tools, and evaluative studies remained underrepresented. The conclusions drawn indicate that Indonesian research on self-harm has expanded rapidly yet remains largely descriptive, thereby underscoring the need for nationally representative prevalence studies, the development and rigorous evaluation of culturally grounded counseling interventions, cross-database triangulation to enhance visibility, and the systematic embedding of guidance and counseling practices into intervention research to advance both scientific relevance and practical impact. Nevertheless, this study is limited by its reliance on a single database (Google Scholar), a single-reviewer screening process, and citation-based indicators that may not be directly comparable with WoS/Scopus metrics.